Beyond Good Intentions: Designing CSR Initiatives for Greater Social Impact - Barnett, Michael L.; Henriques, Irene; Husted, Bryan W. (Journal of Management, 2020)
Are corporate social responsibility (CSR) initiatives providing the societal good that they promise? After decades of CSR studies, we do not have an answer. In this review, we analyze progression of the CSR literature toward assessing the performance of CSR initiatives, identify factors that have limited the literature’s progress, and suggest a new approach to the study of CSR that can overcome these limits. We begin with comprehensive bibliometric mapping illustrating that although social impact has infrequently been its explicit focus, the CSR literature has measured outcomes other than firm performance, especially in the current decade. Thereafter, we conduct a more fine-grained analysis of recent CSR studies. Adapting a logic model framework, we show that even the most highly cited studies have stopped short of assessing social impact, often measuring CSR activities rather than impacts and focusing on benefits to specific stakeholders rather than to wider society. In combination, our analyses suggest that assessment of the performance of CSR initiatives has been driven by the availability of large, public secondary data sources. However, creating more such databases and turning to “big data” analyses are inadequate solutions. Drawing from the impact evaluation literature of development economics, we argue that the CSR field should reconceive itself as a science of design in which researchers formulate CSR initiatives that seek to achieve specific social and environmental objectives. In accordance with this pursuit, CSR researchers should move toward “small data” research designs, which will enable studies to better determine causation rather than just identify correlation.